Study of The Early Social Economic Environment of The Community in The Area of The Pala Plantation Development Plan - Rosita (Journal of Business, Management, & Accounting, 2021)
This study aims to determine the initial socio-economic conditions of the community regarding productive age who have not worked, the number of existing businesses and the level of income of local communities in the area of ​​the planned nutmeg plantation development by Kopermas Kami Nassey in Nikiwar District, Teluk Wondama Regency. The research method is a quantitative method and a qualitative descriptive method. The sampling technique used is simple random sampling. Data collection of productive age who has not worked, the number of existing businesses and the level of income of the community is carried out by means of structured interviews based on questionnaires, while employment data is obtained from government documents. The research subjects are community members who live in 5 villages within the boundaries of the study area. The sample of the community as respondents was determined purposively with the proportion of each village being (50%) of the number of households in the village pole. From the 5 study villages, 63 samples were obtained purposively representing the oldest village heads, village heads, religious leaders, community leaders, schoolteachers, youth leaders, and women leaders. The results showed that the total population in the study area amounted to 1069 people. More than 700 people in the study area are of working age population but job opportunities in this area are very limited due to the low level of the real economy sector that can create job opportunities for local communities. The real sector in the form of productive economic enterprises in this region is very low. Sources of income are relatively few and are classified as low or still below the needs of a decent living in West Papua Province.